Determinants of Organizational Commitment and its Implications for Employee Performance in Coal Mining Companies in Lahat, South Sumatra (Architecture Image Studies, 2026)
This study aims to investigate and assess how Transformational Leadership, Organizational Culture, and Perceived Organizational Support impact Organizational Commitment, and explore the subsequent effects on Employee Performance in three coal mining companies located in Lahat, South Sumatra. The study employs a quantitative causal approach, utilizing Structural Equation Modeling (SEM) based on LISREL for data analysis. The findings reveal that all independent variables—Transformational Leadership, Organizational Culture, and Perceived Organizational Support—significantly and positively influence Organizational Commitment. Additionally, Organizational Commitment is found to have a notable positive impact on Employee Performance. Mediation analysis proves that Organizational Commitment functions as a full mediating variable, where the indirect influence of Organizational Culture and Perceived Organizational Support on Employee Performance through Organizational Commitment is greater than its direct influence. Perceived Organizational Support, with its dimension of welfare support, is the most dominant determinant of Organizational Commitment. Managerial implications suggest a focus on improving employee welfare and artifacts (work tools) to enhance commitment and performance.